Growth Hormone Gene Polymorphism and Its Association with Partial Cumulative Milk Yields of Holstein Friesian Dairy Cattle - R Misrianti; A Anggraeni; E Andreas; C Sumantri (Media Peternakan, 2012)
Growth hormone gene (GH gene) plays an important role in regulating body growth and in developing mammary gland, similar with its interaction to specific receptors. The GH gene has been considered as one of candidate gene associated with selection on lactation trait and milk production. This study was aimed to determine genetic polymorphism of the GH-AluI gene and to associate its genotype variants on various 15-d partial cumulative milk yields in Holstein Friesian (HF) dairy cows. A number of 370 blood samples were collected from six HF populations, respectively from small dairy farmer under the supervision of the North Bandung Milk Cooperation (NBMC) in Cilumber (98) and Pasir Kemis village (96), Dairy Cattle Breeding and Improvement Station (Cikole DCBIS) Cikole (88), Lembang Artificial Insemination Center (Lembang AIC) (17), Singosari Artificial Insemination Center (Singosari AIC (32), and Cipelang Livestock Embryo Center (Cipelang LEC) (40). A polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) method was used to identify variant genotypes of the GH gene using AluI restriction enzyme. Genotyping results produced only two genotypes, i.e. LL and LV genotypes, without VV genotype. Frequency of the former was dominant, whilst that was low for the latter (89% vs. 11%); leading to the frequency of L allele was very high (94%) compared to that of V allele (6%). No significant association between variant genotypes (LL and LV) and various 15-d partial cumulative milk yields.